KEAMANAN INFORMASI DI RUMAH SAKIT - Mohamad Nur Afi (JURNAL SABHANGA, 2020)
The health sector is one of the fields of work that is closely related to privacy issues or a person's personal data, especially data or information from patients. So that the health sector becomes one of the three fields that are very vulnerable to data or information leakage. The latest incident related to patient information is the alleged theft of citizen data related to Covid-19 by hackers sold on the dark web Rapid Forums forum. The data sold are complete, some of the information is in the form of name, citizenship status, date of birth, age, telephone number, home address, population identification number (NIK), and address of the corona test results, where the information is generally also submitted by the patient or asked when registering to health services, both at the Community Health Center (Puskesmas), Polyclinic, or at the Hospital (RS). Therefore, in the health sector itself, it is necessary to implement an information security management system, starting from the patient registration process until the data or information is accessed or stored.